STRATEGI PEMBENTUKAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB PADA SISWA KELAS RENDAH SEKOLAH DASAR MELALUI PEMBIASAAN HARIAN DI LINGKUNGAN SEKOLAH SDN 1 CIMAHPAR - Siti Nuraeni; Asep Sahrul Gunawan (STKIP Subang, 2026)
The development of discipline and responsibility is an important goal in elementary education, especially for lower grade students. At this stage of development, students are in a potential period to instill character values ​​that will influence their future behavior. One effort that can be done to instill character values ​​is through various activities carried out repeatedly and consistently. This study aims to describe the strategy for developing discipline and responsibility in lower grade students at SDN 1 Cimahpar through daily habits in the school environment. The method used in this study is a qualitative approach with a descriptive research type. Data collection techniques were carried out through observation, interviews, and documentation of habituation activities carried out at school. The subjects in this study were the principal, teachers and students. The results of the study indicate that daily habits carried out in a planned and continuous manner are able to foster discipline and responsibility in students at SDN 1 Cimahpar. Forms of these habits include arriving at school on time, carrying out class duty, praying before and after learning, maintaining the cleanliness of the school environment, complying with school rules and completing assignments given by teachers. Furthermore, teacher role models and positive reinforcement of good student behavior contribute to the success of the character building process. Furthermore, conducive school support and collaboration between teachers and parents strengthen the habituation process. Thus, the development of discipline and responsibility in lower grades can be effectively developed through consistent daily habituation activities within the school environment.